Saint Kitts and Nevis - OECS Fiscal Issues : Policies to Achieve Fiscal Sustainability and Improve Efficiency and Equity of Public Expenditures - World Bank (Washington, DC, 2013)
Despite high levels of per capita incomes and good social service provision, poverty remains a persistent problem in St. Kitts and Nevis. To improve competitiveness, restore rapid economic growth, and ensure its medium-term sustainability in the context of the currency union, the main challenges to the St. Kitts and Nevis government are to (a) tighten fiscal policy, notably through expenditure cuts; (b) increase the efficiency of public investments and public service delivery; (c) strengthen regulation and efficiency of public utilities and sea/air transport; and (d) promote education and skills development to prepare the population, notably the poor, to take advantage of new opportunities in the global environment. The report is organized as follows: Chapter 1 discusses fiscal sustainability in St. Kitts and Nevis and presents options for fiscal consolidation; Chapter 2 discusses the role of the business cycle in the design of fiscal policy by reviewing the cyclical components of the fiscal accounts; Chapter 3 discusses the budget management system in place and its effect on budgetary outcomes; Chapter 4 examines the Public Sector Investment Program; Chapter 5 discusses public sector employment and compensation; Chapters 6 and 7 examine public expenditures and outcomes in the education and health sectors; and Chapter 8, the final chapter, discusses social protection programs.